Clinical Analysis of Blepharospasm and Apraxia of Eyelid Opening in Patients with Parkinsonism - Yoon, Won Tae (Korean Neurological Association, 2005)
BACKGROUND AND PURPOSE: Blepharospasm (BSP) and apraxia of eyelid opening (AEO) have been reported as dystonia related with parkinsonism. However, systematic analysis of clinical characteristics of BSP and AEO in parkinsonism has been seldom reported. To investigate the clinical characteristics of BSP and AEO in parkinsonism and to find out the clinical significance to differentiate parkinsonism. METHODS: We enrolled 35 patients who had BSP with or without AEO out of 1113 patients with parkinsonism (913 IPD, idiopathic Parkinson's disease; 190 MSA, multiple system atrophy, 134 MSA-p, 56 MSA-c and 10 PSP, progressive supranuclear palsy). We subdivided MSA into MSA-p (predominantly parkinsonism) and MSA-c (predominantly cerebellar) according to the diagnostic criteria proposed by Quinn. We analyzed the clinical features of BSP and parkinsonism including onset age, onset interval to BSP, characteristics of BSP, presence of AEO, coexisted dystonias on the other body parts, severity of parkinsonism and relationship with levodopa treatment. RESULTS: BSP with or without AEO were more frequently observed in atypical parkinsonism (PSP, 70%; MSA-p, 11.2%; MSA-c, 8.9%) than in IPD (0.9%). Reflex BSP was observed only in atypical parkinsonism (4 MSA-p, 1 MSA-c and 2 PSP). BSP preceding parkinsonism (Pre-BSP) was observed mainly in atypical parkinsonism (2 MSA-p, 1 MSA-c, 1 PSP and 1 IPD). The presence of AEO was more frequent in atypical parkinsonism than in IPD, but isolated AEO was not detected. BSP related to levodopa ('off' symptom or 'peak-dose' effect) were observed only in IPD. CONCLUSIONS: Reflex BSP, Pre-BSP and the presence of AEO may be a unique feature of atypical parkinsonism. BSP related to levodopa might be representative of IPD. No differences were found in the clinical features of BSP between MSA-p and MSA-c.